Sistem Kendali Pestisida Berdasarkan Luas Lahan Pada Tanaman (Studi Kasus : Tanaman Sawi) - Risny Sari Gumala; Suhery, Cucu; Suhardi, Suhardi (Teknik Komputer Politeknik Negeri Sriwijaya, 2024)
Pesticides are crucial compounds that farmers require to manage pests attacking plants. However, if the pesticide dosage is misapplied or does not adhere to recommendations, it can harm plants and the environment. Utilizing variable land area implies that the necessary pesticide dosage varies. A prevalent approach for farmers to estimate the required dosage is by roughly using pesticide bottle caps. Due to approximate measurements, there is potential for excessive or insufficient pesticide doses that do not align with recommended limits. Therefore, a system is needed to control pesticide dosages based on the plant area's requirements. This research establishes a system capable of regulate the necessary pesticide dosage, encompassing the volume of pure pesticide and water. The results of this research show that the level of accuracy of pesticide dosage for the required volume of pure pesticide is 97.82%, provided that the minimum system output is 20 ml and above. Meanwhile, the accuracy of pesticide dosage for water volume requirements reached 98.9%. In addition, the system succeeded in controlling the pesticide dose according to recommendations for spraying mustard greens with an overall control accuracy of 97.47%.